2019
DOI: 10.31234/osf.io/p5z9u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Avoidance of tobacco health warnings? An eye-tracking approach

Abstract: Aims: Across three eye-tracking studies, we examined how the location, framing, immediacy, and severity of health warnings on branded cigarette packs affected visual attention and self-reported avoidance of and reactance to warnings. Design: Study 1: smoking status × warning immediacy (short-term vs. long-term) × warning location (top of back vs. bottom of pack). Study 2: smoking status × warning framing (gain-framed vs. loss-framed) × warning format (text-only vs. pictorial). Study 3: smoking status × warnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…A 20 s exposure was used to ensure adequate exposure of the tobacco GHW warnings to participants across each of the 14 GHW treatments for the subsequent analysis of variance (ANOVA) analysis. The 20 s exposure was in line with past tobacco eye-tracking studies (Kaufman et al , 2018) using similar fixed exposure timings ranging from 10 s (Sillero‐Rejon et al , 2019), 30 s (Lochbuehler et al , 2016) and 44 s (Bansal-Travers et al , 2016).…”
Section: Methodssupporting
confidence: 67%
“…A 20 s exposure was used to ensure adequate exposure of the tobacco GHW warnings to participants across each of the 14 GHW treatments for the subsequent analysis of variance (ANOVA) analysis. The 20 s exposure was in line with past tobacco eye-tracking studies (Kaufman et al , 2018) using similar fixed exposure timings ranging from 10 s (Sillero‐Rejon et al , 2019), 30 s (Lochbuehler et al , 2016) and 44 s (Bansal-Travers et al , 2016).…”
Section: Methodssupporting
confidence: 67%
“…Enhancing gambling warning labels with similar fear-based appeals, especially ones which maintain people's self-efficacy (27), may serve as an even more effective behavior change mechanism in gambling, as the tobacco literature suggests (28).…”
Section: The Present Paper Focused On Education As a Regulatory Goalmentioning
confidence: 99%
“…Visual attention to warnings is, therefore, a critical first step in warning engagement [10,14,15]. Eye‐tracking is considered a gold standard objective measure of attention to tobacco warnings [14,16–18]. Our previous research found that whereas daily smokers avert their gaze from warnings (i.e., avoid warnings), standardised tobacco packaging increases visual attention to health warnings among non‐smokers and non‐daily smokers [9,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Before this, however, warnings must first be noticed and must provoke a series of reactions (e.g., negative affect) [10,12]. Visual attention to warnings is, therefore, a critical first step in warning engagement [10,14,15]. Eye‐tracking is considered a gold standard objective measure of attention to tobacco warnings [14,16–18].…”
Section: Introductionmentioning
confidence: 99%